Pramipexole in the treatment of unipolar and bipolar depression. A systematic review and meta-analysis - Tundo, A; De Filippis, R; De Crescenzo, F (Wiley, 2019)
Objective Several depressed patients do not respond to traditional antidepressants. Our aim was to systematically review the effectiveness and safety of pramipexole in unipolar and bipolar depression. Methods We conducted a systematic review of randomized clinical trials (RCTs) and observational studies on pramipexole for patients with major depressive episodes, following PRISMA guidelines. Our primary outcome measure was treatment response at endpoint. The study protocol was registered on PROSPERO: CRD42018108699. Results We found five RCTs, three open‐label trials and five observational studies, with 504 participants (57% women; mean age, 45.3 years; mean sample size, 39; median duration of treatment, 8 weeks; mean follow‐up duration, 45 weeks; mean maximum dose, 1.62 mg). We found an overall short‐term response rate of 52.2% and remission rate of 36.1%, and an overall long‐term response rate of 62.1% and remission rate of 39.6%. In RCTs, patients treated with pramipexole had a superior response rate compared with placebo (RR: 1.77; 95% CI: 1.11–2.82) and similar to SSRIs (RR: 0.93; 95% CI: 0.44–1.95). Acceptability and tolerability were good, with nausea being the most frequent side‐effect. Conclusion Our study found some evidence for an effect of pramipexole for the treatment of major depressive episodes.